A Polydopamine-Coated Platinum Nanoplatform for Tumor-Targeted Photothermal Ablation and Migration Inhibition - Zou, Xianwen; Ma, Guiqi; Zhu, Pengyu; Cao, Yutao; Sun, Xiao; Wang, Haijun; Dong, Jian (Frontiers in Oncology, 2022)
In this work, Arg-Gly-Asp (RGD) peptide-coupled polydopamine-modified mesoporous platinum nanoparticles (mPt@PDA-RGD NPs) were developed for targeted photothermal therapy (PTT) and migration inhibition of SKOV-3 cells. mPt@PDA-RGD NPs with obvious core/shell structure demonstrated high photothermal performance under 808 nm near-infrared (NIR) laser irradiation. mPt@PDA-RGD NPs with favorable biocompatibility exhibited remarkable SKOV-3 inhibition ability under NIR laser irradiation. Moreover, compared to mPt@PDA NPs, the RGD-functionalized NPs achieved more tumor uptake and PTT performance, which ascribing to the specific interaction between RGD of NPs and αvβ3 integrin overexpressed by SKOV-3. Importantly, cell scratch experiments indicated that the photothermal effect of mPt@PDA-RGD can effectively inhibit the migration of survived SKOV3 cells, which was assigned to disturbance of the actin cytoskeleton of SKOV-3. Thus, mPt@PDA-RGD NPs presented great potential for targeted tumor photothermal ablation and migration inhibition.